(untitled) (Advances in Civil and Architectural Engineering, 2024)
This study presents the preliminary results of a small-scale masonry wall thermal resistance (R-value) measurement. Two small-scale masonry walls were constructed using regular and antimony tin oxide (ATO)-containing bricks. ATO has shown potential for improving the protection against electromagnetic radiation penetration. R-values of the walls were measured using a FluxDAQ device equipped with a heat flux sensor and two temperature sensors for obtaining the heat flux and inside and outside temperatures during the measurement. Furthermore, the thermal conductivity (λ) of the bricks was measured by using the Fox200 Heat Flow Meter. Both results can be used for determining a walls’ thermal transmittance (U-value), which is often used for describing the energy losses and as a measure of a wall’s energy efficiency. This research sought to investigate whether there is a correlation between the results obtained by the small-scale masonry wall and Fox200 device. Ultimately, this experiment aims to verify whether the small-scale masonry wall non-standard method described herein can provide approximately similar results to the standardised method.